Mastering financial modeling in Microsoft Excel: A Practitioner guide to applied corporate finance - Day, Alastair L. (Noida (U. P.) Pearson India education services Pvt. Ltd., 2009)
With every major choice we face we "run through the numbers" to guide our decision-making and legitimise the outcomes. Financial modelling helps managers to make more informed decisions and, crucially, win corporate commitment for those decisions. The ability to construct useful financial models with speed and accuracy is becoming a key skill for all executives to master.